2022
DOI: 10.34198/ejms.11123.115143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature Fluctuations on Darcy-Forchheimer Flow of Oil-Based Nanofluid with Activation Energy and Velocity Slip

Abstract: The effects of fluctuating temperature on Darcy-Forchheimer flow of oil-based nanofluid with activation energy and velocity slip has been analyzed. Similarity transformation was used to transform the governing partial differential equations into coupled nonlinear ordinary differential equations and solved numerically with the aid of the fourth order Runge-Kutta algorithm with a shooting technique. Results for the embedded parameters controlling the flow dynamics have been tabulated and illustrated graphically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Because it offers a more accurate picture of how flow behaves in porous media, the Darcy-Forchheimer model has seen extensive usage in the research of magnetohydrodynamics Maxwell flow over a stretching sheet [5]. Because it takes into account both viscous and inertial forces in porous media, the Darcy-Forchheimer model is an excellent choice for analysing the behaviour of fluids in circumstances in which both forces play a substantial role, such as MHD Maxwell flow over a stretching sheet [6,7]. Studies have demonstrated that the Darcy-Forchheimer model provides a better understanding of the flow behaviour in porous media compared to the standard Darcian model.…”
Section: Introductionmentioning
confidence: 99%
“…Because it offers a more accurate picture of how flow behaves in porous media, the Darcy-Forchheimer model has seen extensive usage in the research of magnetohydrodynamics Maxwell flow over a stretching sheet [5]. Because it takes into account both viscous and inertial forces in porous media, the Darcy-Forchheimer model is an excellent choice for analysing the behaviour of fluids in circumstances in which both forces play a substantial role, such as MHD Maxwell flow over a stretching sheet [6,7]. Studies have demonstrated that the Darcy-Forchheimer model provides a better understanding of the flow behaviour in porous media compared to the standard Darcian model.…”
Section: Introductionmentioning
confidence: 99%